KELALAIAN NOTARIS DALAM PEMBUATAN AKTA AUTENTIK BERDASARKAN PUTUSAN MAHKAMAH AGUNG R.I NOMOR 2604 K/Pdt/2019 - M.Faisal Rahendra Lubis; Tajuddin Noor (Fakultas Hukum, Universitas Samudra, 2022)
A notary is a public official of the state who is given the right and authority to make state documents or deeds that are needed by the public to obtain legal recognition and validity. A Notary cannot refuse an application for a deed and can be sued if he refuses without a clear reason as per the code of ethics of his position as a Notary. The type of research in this study is normative juridical with a research study approach to dispute cases in Decision Number 2604 K/Pdt/2019 concerning Notary Accountability for Negligence in making Authentic Deeds that occurred in Banjarmasin, a Notary is considered to have been negligent in carrying out his duties because he violated the provisions of Article 16 Paragraph (1) letter m. In the decision, the Panel of Judges stated that the Notary is obliged to withdraw/cross/delete the Deed that has resulted in a loss in the agreement. Conclusions on negligence caused by a Notary in carrying out his duties resulted in an Authentic Deed which has a strong evidentiary value turned into an underhand deed. Of course this reduces the privilege of the Authentic Deed, so the regulation regarding sanctions for violations in making the Authentic Deed must be strengthened, so that the Notary upholds the nature of prudence and vigilance in carrying out his duties. As well as a lack of understanding of the procedure for reporting losses to Notaries, socialized more clearly.